Shoot and Root Induction from Cotyledon of Impatiens balsamina. - Rahmat, Zaidah; Mohd. Taha, Aishah; Wagiran, Alina; Huyop, Fahrul Zaman (2005)
Several parameters influenced the regeneration process such as the source of explants was investigated in Impatiens balsamina shoot regenerative system. In the plant tissue culture study of Garden Balsam, I. balsamina, cotyledon was used as the source of explants. Several parameters including the effect of age, section and hormones on shoot and root induction were observed. The cotyledons from in vitro seedling were harvested at different ages of 7, 14 and 21 days with proximal and distal sections. The present study showed that proximal sections from 7 days old seedling in 1 mg/L BAP showed high percentage of shoot production (88%) compared to 14 (86%) and 21 (81%) days old seedlings. The use of distal sections showed formation of callus for all explant ages. Comparison of different hormones concentrations used on shoot induction showed the optimal shoot formation was on MS media with 1 mg/L BAP. For root induction, explants cultured on half strength MS media containing 0.1 mg/L IAA induced the highest rooting percentage (92%). The in vitro plantlets were obtained on free-hormone media at a range of 7 to 10 weeks.